Anonymity, pseudonymity, and the agency of online identity: Examining the social practices of r/Gonewild - Van der Nagel, Emily and Frith, Jordan (First Monday, 2015)
A debate is currently raging regarding the value of anonymity online. On one side of the debate is Facebook, the world’s largest social network site. Facebook demands that people use their real names and is one of the leading forces behind the push towards a “real name” Internet. On the other side of the debate are scholars such as danah boyd and Bernie Hogan and sites such as 4chan and Reddit that view anonymity and pseudonymity as important to how people construct identity online. While much has been written about the benefits of anonymity and pseudonymity, there is a lack of published research examining specific practices enabled by pseudonyms. This paper provides a detailed account of the behaviors enabled through pseudonymous identity construction through a case study of the subreddit r/gonewild. The main contribution of the article is to provide a specific account of the costs of a totalizing embrace of the “real name” Internet.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTIxMC9mbS52MjBpMy41NjE1